Strengthening customer engagement through religious value co-creation / Ken Sudarti and Olivia Fachrunnisa - Ken Sudarti; Olivia Fachrunnisa (2022)
Value co-creation activities involve and benefit three parties at once, namely: the company, employees, and customers. Based on the customer's perspective, involvement during the value co-creation process causes their needs to be met during their participation. This study aims to examine the relationship between Religious Value Congruence (RVC) and Religious Value Co-Creation (RVCC) on Customer Engagement (CE). This study focuses on value creation that occurs when frontline employees and customers meet in interactive marketing activities due to the inherent inseparability of services. This concept was initially only considered a company activity but later developed into value co-creation, a continuous interaction between two or more parties in building a personalized service experience Review on value co-creation, the search for meaning in the value creation process as proposed by previous research has not touched the religious aspect. RVCC is a new concept resulting from the synthesis of the concept of value co-creation with Islamic values. Furthermore, 187 sharia insurance customers spread across several big cities in Central Java, Indonesia, were investigated and examined for the regression relationships using Partial Least Square Structural Equation Modeling (PLS-SEM). The results of data analysis show that Religious Value Congruence can increase the intensity of customers to be involved in Religious Value co- Creation, which ultimately has an impact on strengthening Customer Engagement. The results of this study succeeded in completing the concept of Value Creation proposed by previous researchers by considering religious factors in creating shared values. Religious value co-creation can be the basis for the differentiation of religious-based product offerings because the value received by customers is not only at the level of physical needs but also spiritual needs.